Livelihood implications of in situ-on farm conservation strategies of fruit species in Uzbekistan - Gotor, Elisabetta; Bellon, M.R.; Turdieva, M.K.; Baymetov, K.I.; Nazarov, P.; Dorohova-Shreder, E.; Arzumanov, V.; Dzavakyants, M.; Abdurasulov, A.; Chernova, G.; Butkov, E.; Caracciolo, Francesco (Springer, 2018)
The aim of this paper is to analyze the impact of a set of interventions related to on-farm/in situ conservation and use of fruit species (cultivated and wild) on farmers’ livelihoods and species diversity in Central Asia. Specifically, a difference-in-differences propensity score matching is used to evaluate the outcome of a development research program in Uzbekistan between 2005 and 2010. Species crop diversity maintained by farmers before and after the project increased as a result of the interventions, showing the efficacy of the interventions promoted by the projects in terms of conservation. Furthermore, innovations provided by the program increased both household propensity of marketing and self-consumption of target fruit. However, the program’s interventions did not seem to impact significantly any of the indicators related to household livelihoods. The short time elapsed between the end of the project and the impact assessment may be too brief to capture any observable impact on livelihoods.